Efektivitas Pembelajaran Menggunakan Penilaian Portofolio - Magdalena, Ina; Aciakatura, Chico; Putri, Widia Ananda; Azzizah, Fitri Nur (Lembaga Yasin AlSys, 2023)
Implementation of assessment is an important part of the learning process related to the achievement of student learning outcomes. A good assessment method can make a positive contribution to the teaching and learning process and will have an impact on student learning outcomes. However, student learning outcomes cannot only be measured by grades through written tests, so that the quality of learning can develop better, a portfolio assessment is needed. which is part of the classroom assessment currently being developed. By applying an alternative assessment, one of which is a portfolio assessment of students, can collect evidence of actual student progress that can be used as material for consideration to improve the learning process further. Besides Therefore, assessments like this are felt to be fairer and more transparent for students and can increase student motivation to be actively involved in the learning process.